THE SYNTAX ANALYSIS IN RELATIVE CLAUSE FOUND IN THE NOVEL ENTITLED “BUDDHA” - I Made Juliarta; I Gede Nika Wirawan (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research paper analyses relative clause and its syntax structure found in the novel entitled “Buddha”. The novel entitled “Buddha” is a literary work by Karen Armstrong. There are many data containing English relative clauses found in the novel entitled “Buddha”. Based on the phenomena, the researcher was interested in analyzing relative clauses found in the data source. Theory that was used in analyzing data was proposed by Quirk (1985), Sneddon (1996) and this was supported by other theories. The theory that was used to analyze the syntax structure was the theory proposed by Brown and Miller. This research study applied qualitative method in the process of analyzing data. The data containing English relative clauses were taken from the novel entitled “Buddha”. This research study aims to: (i) analyze the syntax structure in the relative clause found in the novel entitled “Buddha”, (ii) analyze the types of relative clauses in the relative clauses found in the novel entitled “Buddha”.